Peran Faktor Psikologis dalam Proses Pembelajaran: Membangun Kesuksesan di Dunia Pendidikan - Farid, Abdul; Deliani, Nurfarida; Batubara, Juliana (UNIVERSITAS PGRI TULUNGAGUNG, 2023)
This article aims to find out the Role of Psychological Factors in the Learning Process: Building Success in Education. the research conducted in this article is field research using a descriptive qualitative approach. The results showed that Building Success in the World of Education first Self-Efficacy as a Driver of Learning Motivation, Emotional Intelligence to Improve Social Interaction, Psychological Well-Being as a Positive Mental Foundation, Contribution to Improving the Quality of Education if these psychological aspects have run optimally, of course it leads to success in the world of education.